Effects of environment disclosure on capital cost of listed companies on Vietnamese stock market - Le Xuan Quynh; Nguyen Ngoc Tien; Le Thy Ha Van; Nguyen Tra Ngoc Vy (My University, 2020)
Effects of environment disclosure on capital cost of listed companies on Vietnamese stock market
Keywords: Environment disclosure; Capital cost; Listed companies